Preparation method and application of serpentine two-dimensional nanosheets

Through the improved preparation method, efficient single-layer serpentine two-dimensional nanosheets were successfully obtained, which solved the problems of high energy consumption, low chemical reagent pollution and peeling efficiency in the prior art, and achieved heavy metal ions removal with high adsorption amount and adsorption rate, without secondary pollution and easy recovery.

CN116173893BActive Publication Date: 2025-03-11CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310129940.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-17
Publication Date
2025-03-11
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

The existing preparation methods of serpentine nanosheets have problems such as high energy consumption, contamination of toxic chemical reagents, residue and peeling efficiency, which affects its heavy metal ion adsorption removal efficiency.

Method used

Serpentine powder was obtained by crushing, sieving and grinding, and dispersing with isopropanol and ultrasonic peeling, centrifugation and drying to prepare a single-layer structure of serpentine two-dimensional nanosheets to avoid chemical reagent residues and improve yield and adsorption performance.

Benefits of technology

The prepared serpentine two-dimensional nanosheets have high specific surface area, good stability, and wide pH range, which significantly improves the adsorption amount and adsorption rate of heavy metal ions, and is free of secondary pollution and is easy to recover.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116173893B_ABST
    Figure CN116173893B_ABST
Patent Text Reader

Abstract

The invention discloses a serpentine two-dimensional nanosheet and a preparation method and application thereof, wherein the method comprises crushing, sieving and grinding serpentine to obtain serpentine powder; dispersing the serpentine powder with isopropanol to obtain a serpentine powder suspension; and subjecting the serpentine powder suspension to ultrasonic stripping and drying treatment. The preparation method is simple and feasible, has a high yield, and the preparation process does not involve toxic agents. The obtained serpentine two-dimensional nanosheet is a single-layer structure with a thickness of <1 nm, has the characteristics of high specific surface area, high adsorption capacity, good stability, and no chemical reagent residue. The serpentine two-dimensional nanosheet is used as a heavy metal adsorbent for water body restoration, has a significant restoration effect, is conducive to separation, recovery and reuse, and does not cause secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a heavy metal adsorption material, in particular to a serpentine two-dimensional nanosheet, and also to a preparation method of the serpentine two-dimensional nanosheet and application of the serpentine two-dimensional nanosheet as a heavy metal adsorbent in heavy metal wastewater treatment, belonging to the field of environmental waste treatment. Background Art

[0002] There are many technologies for removing pollutants from water environments, including chemical precipitation, electrochemical reduction, ion exchange, membrane filtration and adsorption. Among these methods, adsorption has attracted attention due to its advantages of high treatment efficiency, fast speed, simple operation and reusability. Therefore, people have designed and synthesized a large number of adsorbents for removing pollutants, such as layered double hydroxides, but artificially synthesized adsorbents usually have complex preparation processes, high energy consumption, difficult regeneration and environmentally unfriendly synthesis processes, which limits their industrial and practical applications.

[0003] Serpentine has the advantages of large specific surface area, good chemical and mechanical stability, layered structure, strong exchange capacity, etc., and has the advantages of stable structure, wide source and low price. It is often used as an adsorbent for the removal of environmental pollutants, especially in the field of heavy metal ion removal. In order to further improve the adsorption capacity of serpentine adsorbent, serpentine can be made into a two-dimensional nanosheet with a larger specific surface area. Chinese patent (CN104326479A) discloses a serpentine nanosheet and a preparation method thereof, but it is necessary to first heat and acid-leach the serpentine to destroy the interlayer connection, and then ultrasonically peel in acid solution, but the serpentine nanosheet obtained by the preparation method has a large average thickness, and there are problems such as high energy consumption, pollution and residue of toxic chemical reagents and low stripping efficiency, especially chemical reagents such as organic acids and surfactants are difficult to remove between the clay mineral layers, which will change the physical and chemical properties of the clay mineral surface.

[0004] In the process of treating pollutants in water environment, residual chemical reagents will seriously affect the adsorption and removal efficiency of serpentine nanosheets for heavy metal ions. At the same time, the modification preparation of high-performance two-dimensional nanosheets usually requires the use of native two-dimensional nanosheets without pharmaceutical ingredients as a substrate, so the residual chemical reagents will affect the surface modification process of the two-dimensional nanosheets, thereby further limiting the scope of subsequent use of two-dimensional nanosheets. Summary of the invention

[0005] In view of the above problems in the prior art, the first object of the present invention is to provide a serpentine two-dimensional nanosheet, which has a single-layer structure and a thickness of <1nm, can provide a large number of active sites and spaces, has a high specific surface area, good stability, and adapts to a wide pH range. It is used for heavy metal adsorption and has the advantages of high adsorption capacity, no secondary pollution, and easy recovery.

[0006] The second object of the present invention is to provide a method for preparing serpentine two-dimensional nanosheets, which has the characteristics of high yield and no chemical reagent residue, simple process, convenient operation, low production cost, and is conducive to large-scale production.

[0007] The third object of the present invention is to provide an application of serpentine two-dimensional nanosheets, where the serpentine two-dimensional nanosheets are used as heavy metal adsorbents in heavy metal wastewater treatment, showing high adsorption rate and high adsorption amount while being easy to recover.

[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing serpentine two-dimensional nanosheets, which comprises crushing, sieving and grinding serpentine to obtain serpentine powder; dispersing the serpentine powder with isopropanol to obtain a serpentine powder suspension; and subjecting the serpentine powder suspension to ultrasonic stripping, centrifugal treatment and drying treatment in sequence to obtain the obtained product.

[0009] In the present invention, isopropanol has good dispersibility for serpentine powder, and the interaction between isopropanol and the surface of serpentine powder is stronger than the cohesive energy of isopropanol molecules, so isopropanol is more inclined to combine with serpentine powder. Ultrasonic waves in ultrasound assistance can generate shear force and cavitation bubbles in liquid, and the powerful energy generated by cavitation bubbles when they break breaks the layered structure of serpentine, so that serpentine powder breaks, and isopropanol molecules with smaller spatial volume are more likely to enter the gaps of serpentine particle defects, that is, through the coordinated treatment of ultrasound and isopropanol, the peeling effect of serpentine two-dimensional nanosheets can be further improved, so that the prepared serpentine two-dimensional nanosheets are all monolayers with a thickness of <1nm, so that serpentine exposes more active sites. At the same time, the present invention has experimentally found that isopropanol as a solvent for ultrasonic stripping can not only improve the stripping yield of serpentine two-dimensional nanosheets, but also the prepared serpentine two-dimensional nanosheets have regular morphology, and isopropanol has a low boiling point and low toxicity, and can be completely removed by simple drying treatment in the subsequent process, and will not remain in the serpentine two-dimensional nanosheets, affecting the adsorption performance of the serpentine two-dimensional nanosheets. A large number of studies have shown that the use of isopropanol to disperse serpentine has unexpected effects relative to other small molecules such as ethanol, water, n-hexane, ethyl acetate and other solvents, and can greatly improve the yield and regularity of serpentine two-dimensional nanosheets.

[0010] As a preferred solution, the crushing controls the particle size of the serpentine to be less than 3 mm.

[0011] As a preferred solution, the grinding controls the particle size of the serpentine to be less than 3 μm. In order to avoid the influence of metal ions caused by the inevitable machine wear during the grinding process, the grinding method is dry mechanical grinding, preferably a three-head grinder. By controlling the serpentine grinding particle size to 3 μm, on the one hand, it is to achieve the expansion of the applicability of the traditional mechanical grinding method, and on the other hand, it is to prevent the mineral from being over-grinded and causing structural damage, which affects the adsorption performance of the serpentine two-dimensional nanosheets.

[0012] As a preferred solution, the sieving controls the particle size of the serpentine to -600 mesh. The sieving method used in the present invention is wet sieving, which can quickly separate the stubborn stones that cannot be ground finely, so that the final serpentine two-dimensional nanosheets have a regular morphology and excellent adsorption performance.

[0013] As a preferred solution, the purity of the isopropanol is above AR grade.

[0014] As a preferred solution, the mass concentration of the serpentine powder suspension is 1-3 mg / mL -1 If the concentration of serpentine powder suspension is too low, it will not only cause ultrasonic energy loss, but also be unfavorable for the collision separation between serpentine nanoparticles; while if the concentration of serpentine powder suspension is too high, efficient separation cannot be achieved.

[0015] As a preferred solution, the power of the ultrasonic stripping is 200-500W, and the time is 1-5h. Generally speaking, low power or too short time of ultrasonic stripping will make the serpentine stripping incomplete, and it is difficult to obtain serpentine nanosheets with high adsorption performance. The greater the power of ultrasonic stripping and the longer the time, the higher the yield of serpentine two-dimensional nanosheets; but too high ultrasonic stripping power or too long ultrasonic time will cause power consumption, and the yield of serpentine nanosheets will no longer increase significantly, and the adsorption performance will not be significantly improved. Therefore, it is further preferred that the ultrasonic power is 300-400W and the time is 3-5h. During ultrasound, the serpentine powder suspension is shaken every 30 minutes to avoid gravity sedimentation of serpentine particles, so that it cannot be completely stripped.

[0016] As a preferred solution, the centrifugal treatment conditions are: first centrifuge at 2000-3000 rpm for 8-12 minutes, take the supernatant, and then centrifuge at 12000-15000 rpm for 30-50 minutes. Low-speed centrifugation can remove most of the unpeeled mineral particles, while high-speed centrifugation can enrich the peeled serpentine two-dimensional nanosheets.

[0017] As a preferred solution, the drying is specifically placed in an oven at 75° C. for 30 minutes. The purpose of drying is to completely remove the residual isopropanol in the solution.

[0018] The invention also provides a serpentine two-dimensional nanosheet obtained by the preparation method.

[0019] As a preferred solution, the serpentine two-dimensional nanosheet is a single-layer structure with a thickness of less than 1 nm.

[0020] The present invention also provides an application of serpentine two-dimensional nanosheets, which are used as heavy metal adsorbents in heavy metal wastewater treatment, and can have a significant repair effect on water bodies polluted by heavy metals. After the material adsorbs heavy metal ions, it is easy to precipitate and flocculate, which is conducive to recycling.

[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0022] 1) The serpentine two-dimensional nanosheet provided by the present invention is a single-layer structure with a thickness of less than 1 nm. It has a high specific surface area, significantly increases the adsorption sites of heavy metal ions, has a high adsorption capacity, and the material has good stability without chemical reagent residues.

[0023] 2) The preparation method of serpentine two-dimensional nanosheets provided by the present invention is simple and feasible, has high yield, does not involve toxic agents in the preparation process, and is easy to realize large-scale production.

[0024] 3) The serpentine two-dimensional nanosheets provided by the present invention are used as adsorbents for heavy metal ions in water body restoration, and the restoration effect is remarkable. After the material adsorbs heavy metal ions, it quickly precipitates and flocculates, and can be separated, recovered, and reused by filtration, without causing secondary pollution.

[0025] 4) The raw material serpentine used in the present invention is a natural clay mineral with low price and wide source.

[0026] 5) The serpentine two-dimensional nanosheet high-efficiency adsorbent described in the present invention has the advantages of high specific surface area, high adsorption capacity, wide pH adaptability range, good stability, no secondary pollution, etc., and can have a very significant repair effect on water bodies polluted by heavy metals. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The natural serpentine particles prepared in Example 1 ( Figure 1 A) and serpentine 2D nanosheets ( Figure 1 B) SEM image. Compared with natural serpentine particles, the serpentine two-dimensional nanosheets prepared in the present invention have regular morphology, obvious layered structure, and a lateral size of 100 to 500 nm, and the specific surface area is significantly improved.

[0028] Figure 2 0.1 mg mL of serpentine two-dimensional nanosheets prepared in Example 1 were dispersed by ultrasonic for 30 minutes. -1Atomic force microscope imaging of the suspension. The results show that the height of the serpentine two-dimensional nanosheets is uniform, with a height of about 0.6 to 0.8 nm, and they are all single-layer nanosheets. The size and thickness of the serpentine two-dimensional nanosheets obtained by peeling are important indicators for evaluating serpentine two-dimensional nanosheets. The serpentine two-dimensional nanosheets obtained in this embodiment are large in size and thin in thickness, which can expose and provide a large number of active sites and internal space. It is a high-quality serpentine two-dimensional nanosheet. According to the BET specific surface area test, the specific surface area of ​​natural serpentine particles is 2.2m 2 g -1 The specific surface area of ​​the prepared serpentine nanosheets is 21.5 m 2 g -1 , which significantly increases the adsorption sites of heavy metal ions and significantly enhances the adsorption capacity of serpentine.

[0029] Figure 3 The X-ray diffraction comparison diagram of the serpentine two-dimensional nanosheet and the natural serpentine particles prepared in Example 1. The results show that only the serpentine phase (25-0645) exists in the natural serpentine particles and the serpentine two-dimensional nanosheet, and the layer thickness of the serpentine two-dimensional nanosheet is significantly reduced, indicating that the present invention successfully prepares a thin serpentine two-dimensional nanosheet that can provide more active sites than natural serpentine particles.

[0030] Figure 4 The infrared spectra of the serpentine two-dimensional nanosheets and natural serpentine particles prepared in Example 1. The 989 cm -1 and 3677cm -1 The absorption bands near 452 cm correspond to the stretched -OH groups bound to Mg in octahedral coordination and are characterized by planar deformation and asymmetric vibrations. -1 The nearby range is attributed to the Si-O stretching vibration of serpentine itself. The infrared spectrum of the prepared serpentine two-dimensional nanosheets has basically not changed, indicating that there is no chemical residue on the surface and the surface chemical properties have not changed.

[0031] Figure 5 The Raman spectra of the serpentine two-dimensional nanosheets and natural serpentine particles prepared in Example 1. The results show that the serpentine two-dimensional nanosheets only have a Mg-O vibration peak at 471 cm-1, indicating that the serpentine layer is relatively thin and there is no residual pharmaceutical component.

[0032] Figure 6 The single-layer serpentine two-dimensional nanosheets and natural serpentine particles prepared in Example 1 are effective for heavy metal ions (Cd 2+ and Pb 2+ ) is a comparison chart of the adsorption effects. DETAILED DESCRIPTION

[0033] In order to further understand the present invention, the present invention is described in detail below through specific implementation methods to help technical workers in related fields better understand the concept and technical solution of the present invention.

[0034] Example 1

[0035] The serpentine is crushed to control the percentage of the particle size of the serpentine to be -3 mm, and then sieved through a 600-mesh sieve to obtain serpentine powder, and then ground to control the percentage of the particle size of the serpentine to be -3 μm;

[0036] Weigh 0.12g of serpentine powder, place it in a 65℃ oven for 30 minutes to remove the residual moisture on the surface of the particles, and then place it in a centrifuge tube; add 40mL of isopropanol to disperse and obtain a 3mg / mL serpentine powder suspension; place the serpentine powder suspension in an ultrasonic cleaning machine with an ultrasonic power of 360W, ultrasonically treat for 4h, and shake it every 30 minutes to obtain a stripped serpentine solution. The stripped serpentine solution was first centrifuged at 2000rpm for 10 minutes to remove the unstripped mineral particles; after centrifugation, take the supernatant and centrifuge it at 12000rpm for 30 minutes to obtain the stripped serpentine two-dimensional nanosheet. The stripped serpentine two-dimensional nanosheet was placed in a 75℃ oven for 30 minutes to completely remove the residual isopropanol. The yield of the obtained serpentine two-dimensional nanosheet is 10.2%.

[0037] Example 2

[0038] The difference between this embodiment and embodiment 1 is that the ultrasonic treatment time is changed to 1 hour, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 5.6%.

[0039] Example 3

[0040] The difference between this embodiment and embodiment 1 is that the ultrasonic treatment time is changed to 2 hours, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 7.0%.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that the ultrasonic treatment time is changed to 3 hours, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 9.2%.

[0043] Example 5

[0044] The difference between this embodiment and embodiment 1 is that the ultrasonic treatment time is changed to 5 hours, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 10.4%.

[0045] Comparative Example 1

[0046] The difference between this comparative example and Example 1 is that the solvents are ultrapure water, n-hexane, ethyl acetate, chloroform, ethanol, methanol, acetonitrile and tetrahydrofuran, respectively, and the other conditions are the same. The yields of the obtained serpentine two-dimensional nanosheets are 1.8%, 2.1%, 2.3%, 5.2%, 7.8%, 7.1%, 4.3% and 3.6%, respectively.

[0047] Comparative Example 2

[0048] The difference between this comparative example and Example 1 is that the particle size of the serpentine particles is controlled by grinding to +3.0 to -37.5 μm, which is 100%, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 9.0%.

[0049] Comparative Example 3

[0050] The difference between this comparative example and Example 1 is that the serpentine particle size is controlled to be +37.5 to -75.0 μm by grinding to 100%, and the other conditions are the same. The yield of the obtained serpentine two-dimensional nanosheets is 7.8%.

[0051] Application Examples 1-2

[0052] The serpentine two-dimensional nanosheets and natural serpentine particles prepared in Example 1 were used as adsorbent materials for the adsorption of Cd 2+ and Pb 2+ Adsorption is performed as follows:

[0053] Use cadmium nitrate tetrahydrate Cd(NO3)2·4H2O and Pb(NO3)2 to prepare 1000mM cadmium nitrate and lead nitrate solutions, take 4mL and dilute to 100mM cadmium nitrate and lead nitrate solutions in a 50mL volumetric flask, and adjust the solution pH to 5.8. Take 0.05g of the single-layer serpentine two-dimensional nanosheets prepared in Example 1 and Comparative Examples 2 to 4 and natural serpentine particles and place them in 40mL of 100mM cadmium and lead solutions, respectively, shake at 25°C and 180rpm for 8h and then let it stand for 5min. Take the supernatant and filter it through a 0.22μm PTFE filter, and determine its Cd 2+ and Pb 2+ concentration.

[0054] q e =(C0-C e )V / m

[0055] Among them, q e Represents the amount of heavy metal adsorption, μmol g -1 ;

[0056] C0 represents the initial heavy metal concentration, μM;

[0057] C erepresents the concentration of heavy metals in the solution at equilibrium, μM;

[0058] V represents the volume of the solution, mL;

[0059] m represents the mass of the adsorbent, g.

[0060] like Figure 6 As shown, the serpentine two-dimensional nanosheets prepared in Example 1 have a higher affinity to Cd than natural serpentine particles. 2+ and Pb 2 + The adsorption capacity was significantly increased by about 10 times, the removal capacity of cadmium reached 579.8μmol g-1, and the removal capacity of lead reached 559.5μmol g-1, indicating that the serpentine two-dimensional nanosheets prepared by the present invention have high adsorption capacity and efficiency for heavy metal ions.

Claims

1. An application of serpentine two-dimensional nanosheets, characterized in that: Used as heavy metal adsorbent in heavy metal wastewater treatment; The serpentine two-dimensional nanosheets are obtained by crushing, sieving and grinding serpentine to obtain serpentine powder; dispersing the serpentine powder with isopropanol to obtain a serpentine powder suspension; and subjecting the serpentine powder suspension to ultrasonic stripping, centrifugal treatment and drying treatment in sequence. The grinding controls the particle size of the serpentine to be less than 3 μm; The mass concentration of the serpentine powder suspension is 1-3 mg / mL -1 ; The power of the ultrasonic peeling is 200-500W, and the time is 3-5h; The serpentine two-dimensional nanosheet is a single-layer structure with a thickness of less than 1 nm.

2. The use of a serpentine two-dimensional nanosheet according to claim 1, characterized in that: The crushing controls the particle size of the serpentine to be less than 3 mm; The sieving controls the particle size of the serpentine to be -600 mesh.

3. The use of a serpentine two-dimensional nanosheet according to claim 1 or 2, characterized in that: The centrifugal treatment conditions are: first centrifuge at 2000-3000 rpm for 8-12 min, take the supernatant, and then centrifuge at 12000-15000 rpm for 30-50 min.

Citation Information

Patent Citations

  • Serpentine nanosheet and preparation method thereof

    CN104326479A

  • Exfoliation of layered materials

    WO2012101457A1